2007
DOI: 10.5694/j.1326-5377.2007.tb01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in health and health care for Australia

Abstract: The next Australian Government will confront major challenges in the funding and delivery of health care. These challenges derive from: Changes in demography and disease patterns as the population ages, and the burden of chronic illness grows; Increasing costs of medical advances and the need to ensure that there are comprehensive, efficient and transparent processes for assessing health technologies; Problems with health workforce supply and distribution; Persistent concerns about the quality and safety of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
110
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 9 publications
2
110
0
Order By: Relevance
“…14 That study showed that parks located in suburbs of relatively socioeconomically disadvantaged communities had poorer quality and fewer facilities including trees, shade, water features, walking paths, lighting and dog signage. Given the evidence of lower physical activity levels 15 and poorer health outcomes for residents of socioeconomically disadvantaged areas, [16][17][18] and likely benefits of increased contact with greenery and open space, 10 13 strategies such as park refurbishments to improve satisfaction with recreational amenities and increase park usage may have a broader health benefit for these communities.…”
Section: Introductionmentioning
confidence: 99%
“…14 That study showed that parks located in suburbs of relatively socioeconomically disadvantaged communities had poorer quality and fewer facilities including trees, shade, water features, walking paths, lighting and dog signage. Given the evidence of lower physical activity levels 15 and poorer health outcomes for residents of socioeconomically disadvantaged areas, [16][17][18] and likely benefits of increased contact with greenery and open space, 10 13 strategies such as park refurbishments to improve satisfaction with recreational amenities and increase park usage may have a broader health benefit for these communities.…”
Section: Introductionmentioning
confidence: 99%
“…Armstrong et al [1] summarise eight key challenges including a universal recognition of the need to focus on chronic disease prevention and management and demonstrable workforce challenges in regional, rural and remote areas of Australia. These authors state “shortages are more significant in outer metropolitan, rural and remote regions, especially in Indigenous communities, and in particular areas of care such as mental health, aged care and disability” (p.486).…”
Section: Introductionmentioning
confidence: 99%
“…These authors state “shortages are more significant in outer metropolitan, rural and remote regions, especially in Indigenous communities, and in particular areas of care such as mental health, aged care and disability” (p.486). The inequity in the health status of Australians who live in rural and remote Australia is of national concern, with rural and remote Australians having poorer health status, less access to health professionals [2] and less access to private health services [1] than their metropolitan counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Within Australia, one of the greatest recognised health challenges is achieving health equity for all [8]. Cancer patients living in rural and disadvantaged areas are generally more likely to be diagnosed with advanced cancer and have poorer survival outcomes [9,10].…”
Section: Introductionmentioning
confidence: 99%